Attitudes towards gender equality and perception of democracy in the Arab world. Issue 5 (28th July 2016) - Kostenko, Veronica V.; Kuzmuchev, Pavel A.; Ponarin, Eduard D.
Abstract : This article analyses the relationship between support of democracy and attitudes to human rights, in particular, support for gender equality, in the countries covered by the first wave of the Arab Barometer project. We use cluster analysis and negative binomial regression modelling to show that, unlike in most countries of the world, correlation between support of democracy and gender equality is very low in the Arab countries. There is a group of people in the region who support both democracy and gender equality, but they are a small group (about 17% of the population) of elderly and middle-aged people characterized by higher education and social status. A substantial number of poorly educated males express support for democracy but not for gender equality. Many people, especially young males aged 25–35 in 2007, are against both gender equality and democracy. Younger people tend to be both better educated and more conservative, those belonging to the 25–34 age group being the most patriarchal in their gender attitudes. Yet, controlling for age, education does have a positive effect on gender equality attitudes. Nevertheless, this phenomenon may reflect two simultaneous processes going on in the Middle East. On the one hand, people are getting more educated, urbanized, etc., which means the continuation of modernization. On the other hand, the fact that older people are the most liberal age group may point to a certain retrogression of social values in the younger generations.